Perancangan Sistem Autentikasi Jaringan Nirkabel dan File Server menggunakan RADIUS dan WPA2-Enterprise - Tristanto Ari Aji, Tristanto Ari Aji; Kurniawan , Muhammad; Sutanto, Yudi; Slameto, Andika Agus; Kristiary, Ravenusa Arjuna (Jurnal PROCESSOR, 2025)
Network security and efficiency are important aspects in managing network infrastructure, especially in wireless networks that are prone to various forms of attacks. This research aims to design a more secure and efficient wireless network and file server authentication system using the WPA2-Enterprise protocol and a RADIUS server. In this design, the WPA2-Enterprise protocol is used to improve the security of wireless network access with a user identity-based authentication method, not just a generic password. To improve the efficiency of the authentication process, a RADIUS server is used. The RADIUS (Remote Authentication Dial-In User Service) server functions as a centralised authentication centre that verifies user credentials from a predefined database. The system in this research integrates file server service authentication and wireless network usage authentication. Test results show that this design successfully provides more secure authentication, prevents unauthorised access, and simplifies user and access rights management. The use of a RADIUS server and the WPA2-Enterprise protocol allows for flexibility and efficiency in implementing the system in a campus environment. The implementation of this system can be a practical solution in improving the security and efficiency of the wireless network authentication process and internal file server services.